PENGARUH PENGGUNAAN MEDIA POP UP BOOK TEMATIK BERBASIS KEISLAMAN DAN BUDAYA LOKAL PONTIANAK TERHADAP CRITICAL THINKING SKILL PESERTA DIDIK KELAS 5 PADA MADRASAH IBTIDAIYAH NEGERI 1 SAIGON PONTIANAK - Multiani, Berly; Hasmy, Ali; Muskania, Ricka Tesi (Indonesian Journal of Islamic Elementary Education, 2021)
The purpose of this study is to uncover: (1) Critical Thinking Skills early (pre-test) control class learners and experimental classes without the use of thematic pop up book media based on Islam and local culture Pontianak; 2) The use of thematic pop up book media based on Islam and local culture pontianak in order to improve critical thinking skills learners. 3) Critical Thinking Skill learners (post-test) control classes and experimental classes using thematic pop up book media based on Islam and local culture Pontianak.This research includes quantitative research experimental methods. The data sources of this study are population and sample. The population in the study was all class V MIN 1 Saigon Pontianak. The sample in this study was va class learnersand VD MIN 1 Saigon Pontianak, each class numbered 37 learners. The techniques and tools used to collect data are observation techniques, measurement techniques and document studies. The data collection tools used are observation sheets, tests and documents.Based on the analysis conducted, the researcher concluded that: 1) In the hypothesis test the pre-test data obtained which means there is no influence between free variables on bound variables; 2) from the observation of the implementation of the use ofthematic Pop Up Book media based on Islam and local culture pontianak is 100%. 3) In the post-test data hypothesis test of the control class and the experimental class the result which meansaverage difference between the experimental class and the controlclass so that there is an influence of the free variable on the bound variable.